A PhD In motion: Advancing a critical academic mobilities approach (CAMA) to researching short-term mobility schemes for doctoral students. Issue 5 (4th July 2019) - Henderson, Emily F.
ABSTRACT: Short-term mobility has been neglected in the higher education mobilities literature, which tends to focus on longer stays such as study abroad or entire degrees. Short-term doctoral mobility schemes are relatively low-cost, potentially high-value investments in the development of early career researchers. Doctoral mobilities research – and the field of academic mobilities research more broadly – is characterised by a positivist, often atheoretical orientation; this article responds to this by introducing a critical academic mobilities approach (CAMA). This approach is rooted in the 'mobilities paradigm', and involves (i) questioning the status of mobility as a universal good; (ii) exploring the subjectivity of mobile subjects as dynamic and shifting, but also structurally determined; (iii) a commitment to researching mobility processes as well as investments and outcomes. The article explores 'autoethno-case studies' of two doctoral mobility schemes funded by the UK Economic and Social Research Council (ESRC): Overseas Institutional Visits (OIV) and the PhD Partnering Scheme (PPS).